RISK MANAGEMENT STRATEGY AND PRICING COST OF SALES OF THE PRODUCTION PROCESS - Lella Anita (BADAN PENERBIT STIEPARI PRESS, 2022)
Currently, there are still many MSME that still use simple methods in determining the Cost of Goods Sold (HPP). This is due to the lack of knowledge about it. In fact, it is very important for MSME to be able to calculate the Cost of Goods Sold (HPP) according to the provisions in order to be able to determine the selling price and maximize the profit earned. In addition, paying attention to the risks that arise in the production process is also very important to determine the quality of the products produced. Through this community service activity, it is hoped that MSME actors will be able to determine the cost of goods sold and also minimize the risks that arise as a result of the production process.